Cadaveric Study of Different Shapes of the Human Adrenal Glands - Siddiqua, Diruba; Nurunnabi, Abu Sadat Mohammad; Ara, Shamim; Perven, Hosna Ara (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 140-142 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15300